2008
DOI: 10.1021/es8020099
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of Paracetamol: Dominant Reactants, Intermediates, and Reaction Mechanisms

Abstract: The role of primary active species (ecb(-), hvb(+), *OH, HO2*, O2*(-), and H2O2) during photocatalytic degradation of paracetamol (acetaminophen) using TiO2 catalyst was systematically investigated. Hydroxyl radicals (*OH) are responsible for the major degradation of paracetamol with a second-order rate constant (1.7 x 10(9) M(-1) s(-1)) for an *OH-paracetamol reaction. A total of 13 intermediates was identified and classified into four categories: (i) aromatic compounds, (ii) carboxylic acids, (iii) nitrogen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(88 citation statements)
references
References 33 publications
6
81
1
Order By: Relevance
“…To our knowledge, this is the first description of the biodegradation pathway for paracetamol. The initial steps are partially different from the reactions previously described for photocatalytic and electro-Fenton degradation of paracetamol (Brillas et al 2009;Yang et al 2009) (Fig. 5c), in which hydroquinone has been identified as the main transformation products.…”
Section: Proposed Metabolic Pathways Enzymes and Possible Intermedicontrasting
confidence: 55%
See 1 more Smart Citation
“…To our knowledge, this is the first description of the biodegradation pathway for paracetamol. The initial steps are partially different from the reactions previously described for photocatalytic and electro-Fenton degradation of paracetamol (Brillas et al 2009;Yang et al 2009) (Fig. 5c), in which hydroquinone has been identified as the main transformation products.…”
Section: Proposed Metabolic Pathways Enzymes and Possible Intermedicontrasting
confidence: 55%
“…Nowadays, paracetamol wastewater is mainly treated by chemical oxidation processes such as electrochemical (Brillas et al 2005), ozonation (Andreozzi et al 2003), H 2 O 2 /UV oxidation (Andreozzi et al 2003;Skoumal et al 2006), TiO 2 photocatalysis (Yang et al 2008(Yang et al , 2009, and solar photoelectro-Fenton oxidation (Li et al 2007). Although these chemical methods may be available for treating these pollutants, the harsh reaction conditions, the generation of secondary pollutants, and the high operational cost associated with these methods have often made them not a desirable choice (Li et al 2007;Chen et al 2010).…”
Section: Biodegradation Of Paracetamol By Pure Culturementioning
confidence: 99%
“…To our knowledge, this is the first description of the biodegradation pathway for paracetamol. The initial steps are partially different from the reactions previously described for photocatalytic and electro-Fenton degradation of paracetamol (Brillas et al 2009;Yang et al 2009), in which hydroquinone has been identified as the main transformation products. Gusseme et al (2011) also reported that hydroquinone was a temporary transformation product of paracetamol degradation by two bacterial strains, D. tsuruhatensis and P. aeruginosa.…”
Section: Discussionmentioning
confidence: 77%
“…Peak B had the same (n03) retention time and mass spectrum as an authentic sample of derivatized 4-aminophenol. 4-Aminophenol was also indentified as a main intermediate during photocatalytic degradation of paracetamol (Yang et al 2009). …”
Section: Possible Intermediatementioning
confidence: 99%
See 1 more Smart Citation